2006
DOI: 10.1242/jcs.02809
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream formTrypanosoma bruceidepend upon multiple metacaspases associated with RAB11-positive endosomes

Abstract: Trypanosoma brucei possesses five metacaspase genes. Of these, MCA2 and MCA3 are expressed only in the mammalian bloodstream form of the parasite, whereas MCA5 is expressed also in the insect procyclic form. Triple RNAi analysis showed MCA2, MCA3 and MCA5 to be essential in the bloodstream form, with parasites accumulating pre-cytokinesis. Nevertheless, triple null mutants (Δmca2/3Δmca5) could be isolated after sequential gene deletion. Thereafter, Δmca2/3Δmca5 mutants were found to grow well both in vitro in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
102
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 70 publications
6
102
0
5
Order By: Relevance
“…Furthermore, the L. major metacaspase seems to have an essential function in cell-cycle progression rather than in PCD. 28 And, in T. brucei, metacaspases appear to be associated with RAB11-positive endosomes, 15 and not to intervene in apoptosis. Still, intriguingly, some reports have described 'caspase-like' activities in these protozoa.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the L. major metacaspase seems to have an essential function in cell-cycle progression rather than in PCD. 28 And, in T. brucei, metacaspases appear to be associated with RAB11-positive endosomes, 15 and not to intervene in apoptosis. Still, intriguingly, some reports have described 'caspase-like' activities in these protozoa.…”
Section: Discussionmentioning
confidence: 97%
“…Although metacaspase genes have been identified in the genome of all trypanosomatids, their involvement in apoptosis is still debated. [14][15][16][17] Moreover, no homologue for members of the Bcl-2 protein family has been identified in T. brucei. Finally, two genes whose transcription is upregulated late during the identification of concanavalinA-induced PCD in the procyclic form of T. brucei rhodesiense, a homologue of prohibitin and a protein called TRACK, homologous to the RACK family (receptor for activated kinase C).…”
mentioning
confidence: 99%
“…However, in T. brucei bloodstream forms, triple metacaspase null mutants (Dmca2/3, Dmca5) did not prevent cell death induced by prostaglandin D 2 when compared with wild-type parasites. 12 Nevertheless, RNA interference of the three MCAs together resulted in a rapid arrest of growth with a delay in kinetoplast segregation and a cytokinesis block. In addition, Ambit et al 13 showed that limited levels of LmjMCA are essential for normal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…5 Their substrate specificity is for basic residues at P1 position, making them unable to cleave caspase substrates. 6 Evidences suggest that metacaspases modulate cell death, [7][8][9][10][11] cell cycle progression [12][13][14] and protein aggregation, 15 but there is still controversy about their functions and their relation with caspases. [16][17][18] The fact that metacaspases are not present in humans and fulfil important roles in trypanosomatids make them attractive drug targets, and a first series of inhibitors with trypanocidal activity has been developed recently.…”
mentioning
confidence: 99%
“…MCA2, MCA3, and MCA5 have the conserved catalytic residues (histidine/cysteine dyad) (27) and are collectively required for the bloodstream form of the parasite (28). MCA2, which is an active peptidase, is located in RAB11-positive endosomes and has roles in precytokinesis cell cycle control (28).…”
mentioning
confidence: 99%